Impairment in endothelial bioenergetics contributes to diabetes-induced vascular dysfunction - Atawia, Reem T; Bruder do Nascimento, Thiago; Batori, Robert; Kennard, Simone; Antonova, Galina; Ushio-Fukai, Masuko; Fukai, Tohru; Huo, Yuqing; Patel, Vijay S; Fulton, David J R; Belin de Chantemèle, Eric J (The FASEB journal, 2022)
Diabetes, whether insulin-dependent or independent is a major cause of endothelial dysfunction and a leading risk factor for cardiovascular disease. While compelling evidence indicates that endothelial dysfunction is a precursor and contributor to cardiovascular disease, the etiology of diabetes-induced endothelial dysfunction remains ill-defined. Recently alteration in endothelial cell bioenergetics has emerged as a new contributor to vascular diseases. However, whether alterations in endothelial glycolysis, the main endothelial cell bioenergetic pathway contributes to endothelial dysfunction is unknown. Herein, we tested the hypothesis that diabetes-associated endothelial dysfunction involved increases in endothelial cells glycolysis and upregulation of its primary regulator, 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 3 (PFKFB3). Measurement of glycolytic activity via Seahorse analyzer in primary human aortic endothelial cells (HAEC) from control and diabetic patients revealed a significant increase in basal glycolysis in diabetic subjects (p<0.05). We also employed Akita mice, a mouse model of type 1 diabetes. Male Akita mice showed a diabetic phenotype with 3-folds increase in blood glucose. Seahorse analysis in intact aortic explants revealed a 1.7-fold increase in basal glycolysis and a 1.3-fold increase in maximal glycolysis in Akita mice (P<0.05). The increase in glycolysis was endothelial-derived as aortic denudation significantly decreased glycolysis in Akita mice and abolished the difference between groups. No significant difference in mitochondrial function was depicted in the mito-stress test between Akita and WT aortic explants (p>0.05). Additionally, endothelial cells extracted from aortas of Akita mice exhibited a 2-fold increase in PFKFB3 mRNA expression(P<0.05). Interestingly, inhibition of PFKFB3 using 3PO (20μM) restored endothelial function in Akita mice. Similarly, Non-obese diabetic females (NOD), a model for type-1 diabetes, showed 4-fold increases in PFKFB3 mRNA expression in aortic endothelial cells and impaired EDR which was restored with 3PO (p<0.05). To further evaluate the role of PFKFB3 in vascular endothelial function we overexpressed PFKFB3 in WT aortas with adenovirus (Ad-PFKFB3), and reported impaired aorta EDR(P<0.05). Transduction of HAEC with Ad-PFKFB3 showed a significant increase in ROS producing enzyme (NOX1). Also, inhibition of NOX1 using the selective inhibitor GKT771 restored EDR in Akita and Ad-PFKFB3-transduced WT aortas. In Conclusion, our data identified for the first time a role for endothelial glycolysis in the control of vascular relaxation and showed a crucial role of PFKFB3-mediated endothelial glycolysis in vascular endothelial dysfunction associated with Type-1 diabetes in males and females. The underlying mechanism potentially involves NOX1 as a downstream target for PFKFB3. Thus, Inhibitors of PFKFB3 could be a potential therapeutic target for diabetes-induced vascular endothelial dysfunction.